2009
DOI: 10.1140/epjb/e2009-00306-1
|View full text |Cite
|
Sign up to set email alerts
|

Indications for the coexistence of closed orbit and quantum interferometer with the same cross section in the organic metal β′′-(ET)4(H3O)[ Fe(C2O4)3] .C6H4Cl2: persistence of Shubnikov-de Haas oscillations above 30 K

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
3
4
0
Order By: Relevance
“…Effective Landé factor as low as g * = 1.5 ÷ 1.6 are reported for the strongly correlated compound κ-(ET) 2 Cu(NCS) 2[5], nevertheless g * = 2 is consistent with data of other ET salts[17,18].…”
supporting
confidence: 77%
“…Effective Landé factor as low as g * = 1.5 ÷ 1.6 are reported for the strongly correlated compound κ-(ET) 2 Cu(NCS) 2[5], nevertheless g * = 2 is consistent with data of other ET salts[17,18].…”
supporting
confidence: 77%
“…In such a case, 3 Fourier components linked by a linear combination settled by the orbits compensation, F b = Fa + F b−a , should be observed. This picture holds, not only for the above compound under pressure for which F3 = F1 + F2 within the error bars, but also for (NH4, Fe, C3H7NO) in the applied pressure range from ambient pressure to 1 GPa [37,38] and for (H3O, Fe, C6H4Cl2) [33,34,39].…”
Section: Puzzling Oscillations Spectrasupporting
confidence: 59%
“…2(c). Keeping in mind that dHvA oscillations are only sensitive to the density of states, it has been shown that both the field and temperature dependence of the b oscillations are consistently accounted for by the coexistence of a closed b orbit and a quantum interferometer with the same cross section [33,34,39]. Unfortunately, existence of a QI path is not consistent with the FS of Fig.…”
Section: Puzzling Oscillations Spectramentioning
confidence: 93%
“…2 and Ref. 18). For a given magnetic field, the temperature dependence of the oscillation amplitude can be written (see Eqs.…”
Section: Resultsmentioning
confidence: 99%